A review of stirling engine technologies applied to micro-cogeneration systems - Ferreira, Ana C. M. (2012)
This paper presents a review on Stirling engines used in micro-CHP system applications. The aim of this review is to investigate and identify the commercial solutions available in the market based on Stirling engine technology. This should represent a preliminary study to understand what are the best configurations to use with this technology in combined heat and power production for the building sector. A number of Stirling engine configurations and designs, including the engine’s development is provided and discussed. Stirling engines have been identified as a promising technology for energy conversion due to their high efficiency levels, low pollutant emissions, low noise levels and due to their flexibility in terms of fuel sources. Micro-CHP systems based on Stirling engines could be suitable for applications where multi-fuelled characteristics and high thermal efficiencies are needed. Stirling engines are flexible and consistent with the requirements for a sustainable development.